A revision of the Palaeocorystoidea and the phylogeny of raninoidian crabs (Crustacea, Decapoda, Brachyura, Podotremata) - van Bakel, Barry W.m.; Guinot, Danièle; Artal, Pedro; Fraaije, René H.b.; Jagt, John W.m. (Zootaxa, 2012)
Abundant fossil material of extinct brachyurans has revealed morphological details hitherto rarely used inpalaeontological studies. Detailed comparisons between extant and extinct material have been carried out, with anemphasis on thoracic sternum, abdomen and appendages. Documented for the first time is the unique character ofRaninoidea De Haan, 1839, their ‘gymnopleurity’, which is not found in their predecessors, the PalaeocorystidaeLőrenthey in Lőrenthey & Beurlen, 1929. Palaeocorystidae, together with four other families (CamarocarcinidaeFeldmann, Li & Schweitzer, 2008; Cenomanocarcinidae Guinot, Vega & Van Bakel, 2008; Necrocarcinidae Förster, 1968emend.; and Orithopsidae Schweitzer, Feldmann, Fam, Hessin, Hetrick, Nyborg & Ross, 2003a emend.), is assigned hereto the superfamily Palaeocorystoidea, of similar rank to Raninoidea. Both Raninoidea and Palaeocorystoidea are affordeda subsection rank and referred to as subsection Raninoidia De Haan, 1839 emend. New or emended diagnoses areprovided for all higher taxonomic levels, and all members of Raninoidia are listed in an appendix. A unique abdominalholding structure, the double peg, is described for the first time. Its gradual evolution is documented and the phylogeneticimplications are discussed. Comparative morphology of the thoracic sternum, abdominal holding structures, the sternum-pterygostome configuration, respiratory physiology and spermathecae, all reveal polarities of the raninoidian clade. Theconfiguration of the sternum with the pterygostome, which is related to body strength and respiratory physiologicalefficiency, differs significantly between the two superfamilies, Raninoidea showing a derived condition. An evolutionarylineage, leading from Palaeocorystidae, via Lyreididae to Raninidae is recognised, and an intermediate form, Marylyreiduspunctatus n. comb., is discussed. Several hitherto unknown structures in extant raninoids, an obstruction system for theabdomen and a telson protection valve, are documented. The cryptic spermathecal apertures of raninoids, so far barelyunderstood, are re-examined and compared to those of palaeocorystoids. The phylogeny of Podotremata, often debated inthe recent literature, is discussed anew on the basis of these observations. A position of Raninoidea within Eubrachyura,recently claimed by several authors, cannot be maintained, an observation supported by documentation of the basalcondition of Raninoidia. A new basal lyreidid clade, Marylyreidinae n. subfam., is erected, whereas new genera andspecies include Antonioranina n. gen. (Cyrtorhininae), Bournelyreidus teodorii n. gen., n. sp. (Lyreidinae), Cenocorystesbretoni n. sp. (Palaeocorystidae), Cenomanocarcinus cantabricus n. sp. (Cenomanocarcinidae), Eosymethis aragonensisn. gen., n. sp. (Symethinae), Eucorystes iserbyti n. sp., Eucorystes navarrensis n. sp. (both Palaeocorystidae),Ferroranina tamilnadu n. gen., n. sp. (Palaeocorystidae), Joeranina gaspari n. gen., n. sp. (Palaeocorystidae),Marylyreidus n. gen. (Marylyreidinae n. subfam.), Paranecrocarcinus balla n. sp. (Paranecrocarcininae), Symethoidesmonmouthorum n. gen., n. sp. (Symethinae) and Vegaranina n. gen. (Ranininae). Several raninoid and palaeocorystoid genera are revised, and emended diagnoses given.